A survey of current practice in UK emergency department management of patients with blunt chest wall trauma not requiring admission to hospital. Issue 9 (September 2021) - Battle, Ceri; O'Neill, Claire; Newey, Luke; Barnett, Jane; O'Neill, Martin; Hutchings, Hayley
Highlights: There is UK-wide variation in the Emergency Department management of patients with blunt chest wall trauma. Potential areas for improvement include identification of high-risk patients, initial assessment and management strategies. Further research is needed as to whether structured national guidelines would lead to an overall improvement in outcomes. Abstract: Introduction: There is no universal agreement or supporting evidence for the content or format of a standardised guidance document for patients with blunt chest wall trauma. The aim of this study is to investigate current UK Emergency Medicine practice of the management of patients with blunt chest wall trauma, who do not require admission to hospital. Methods: This was a cross-sectional survey study, with mixed quantitative / qualitative analysis methods. A convenience sample of all professions working in the Emergency Departments / Urgent Care Centres in the UK was used. A combination of closed and open-ended questions were included, covering demographics and current practice in the respondent's main place of work. Themes explored included management strategies for safe discharge home, risk prediction and variables considered relevant for inclusion in patient guidance. Results: A total of 113 clinicians responded from all UK trauma networks, including all devolved nations. A total of 20 different risk prediction tools / pathways were reported to be used when assessing whether a patient is safe for discharge home, with over 35 different variables listed by respondents as being important to highlight to patients. Qualitative analysis revealed that a small number of respondents believe patients can be better managed through the improvement of the following; identification of the high-risk patient, initial assessment and current management strategies used in the ED / UCC. Discussion: The wide variation in practice highlighted in this study may be due in part to a lack of national consensus guidelines on how to manage this complex patient group. Further research is needed into whether structured national guidelines for the assessment and management of such patients could potentially lead to an overall improvement in outcomes. Such guidelines should be developed by not only expert clinicians and researchers, but also and more importantly by those service-users who have lived experience of blunt chest wall trauma.